Techno-economic analysis of control strategies for heat pumps integrated into solar district heating systems. (October 2021) - Abokersh, Mohamed Hany; Vallès, Manel; Saikia, Kangkana; Cabeza, Luisa F.; Boer, Dieter
Highlights: A solar district heating system with seasonal storage is examined. Various control strategies for the heat pump operation are investigated. Solar heating fraction over 84% is achievable with a life cycle cost of 67.1 €/MWh. Well-designed heat pump control can bring techno-economic benefits in the district heating. Abstract: This present work focuses on assessing the techno-economic benefits of different control strategies for a heat pump integrated into the solar assisted district heating system (SDHS). The system has been developed using dynamic simulation software (TRNSYS) and optimized based on a genetic algorithm. With an industrial-sized heat pump connected to thermal storage tanks for domestic hot water (DHW) and space heating (SH) for the requirements of the community, a SDHS is operated by applying two different control mechanisms for the heat pump based on its reference operating temperature. The application of the methodology is applied to a residential neighborhood community of 10 buildings located in Madrid to act as a proxy for the Mediterranean climates. The results showed a significant effect for the heat pump control in the techno-economic benefits where the proposed system is able to provide a solar fraction up to 99%. Furthermore, the total electricity consumption of the heating system varied by 10% between the best and the worst cases. Besides, the annual seasonal storage efficiency improved up to 90% with a life cycle expense up to 67.12 Euro/MWh, and a payback period of 29 years.